The psychophysiology of music-based interventions and the experience of pain - Arnold, Carolyn A.; Bagg, Matthew K.; Harvey, Alan R. (Frontiers in Psychology, 2024)
In modern times there is increasing acceptance that music-based interventions are useful aids in the clinical treatment of a range of neurological and psychiatric conditions, including helping to reduce the perception of pain. Indeed, the belief that music, whether listening or performing, can alter human pain experiences has a long history, dating back to the ancient Greeks, and its potential healing properties have long been appreciated by indigenous cultures around the world. The subjective experience of acute or chronic pain is complex, influenced by many intersecting physiological and psychological factors, and it is therefore to be expected that the impact of music therapy on the pain experience may vary from one situation to another, and from one person to another. Where pain persists and becomes chronic, aberrant central processing is a key feature associated with the ongoing pain experience. Nonetheless, beneficial effects of exposure to music on pain relief have been reported across a wide range of acute and chronic conditions, and it has been shown to be effective in neonates, children and adults. In this comprehensive review we examine the various neurochemical, physiological and psychological factors that underpin the impact of music on the pain experience, factors that potentially operate at many levelsthe periphery, spinal cord, brainstem, limbic system and multiple areas of cerebral cortex. We discuss the extent to which these factors, individually or in combination, influence how music affects both the quality and intensity of pain, noting that there remains controversy about the respective roles that diverse central and peripheral processes play in this experience. Better understanding of the mechanisms that underlie music's impact on pain perception together with insights into central processing of pain should aid in developing more effective synergistic approaches when music therapy is combined with clinical treatments. The ubiquitous nature of music also facilitates application from the therapeutic environment into daily life, for ongoing individual and social benefit.